Perlindungan Hukum Terhadap Anak Korban Prostitusi Online Melalui Aplikasi Michat - Hehalatu, Nurhalisa; Hehanussa, Deassy Jacomina Anthoneta; Supusepa, Reimon (PATTIMURA Legal Journal, 2022)
Introduction: This study discusses the legal protection of child victims of online prostitution through the MiChat application Purposes of the Research: Reviewing and discussing forms of legal protection for children who are victims of online prostitution through the MICHAT application and efforts to overcome online prostitution against children. Methods of the Research: This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach. Results of the Research: The results of the study show that online prostitution of children through the Michat application is on the rise, the lack of coordination between agencies, and the lack of legal awareness in this case law enforcement officers, KPAI, NGOs, parents, and other community institutions, causing the handling of cases of online prostitution crimes. not maximal. Preventive efforts and repressive efforts carried out by law enforcement officers have not been able to provide maximum legal protection to children who are victims of online prostitution. Thus, mitigation efforts must be carried out optimally, in order to provide legal protection to children who are victims of online prostitution through the MiChat application